Carbon stocks and sequestration potential in agroforestry system - Normah Awang Besar @ Raffie; Phua, Mui How; Mazlin Mokhtar (Universiti Malaysia Sabah, 2012)
Studies on carbon stock in agroforestry systems has been conducted in Balung River Plantation, Tawau, Sabah. The objective of the study are to determine carbon content of above ground vegetation including crops, shrubs and trees in agroforestry system, to determine carbon content of soil in agroforestry system, to estimate aboveground carbon stock using UDAR data and to estimate carbon sequestration potential in agroforestry system. Three combination of oil palm (Elaeis guineensis) and agarwood (Aquilaria malaccensis) in agroforestry system with different age were investigated. The combinations are oil palm (27 years) and agarwood (7 years), palm oil (20 years) and agarwood (7 years) and oil palm (17 years) and agarwood (5 years). Oil palm plantation (16 years) and forest reserve was investigated as a control. Agroforestry system of teak (Tectona grandis), agarwood (Aquilaria malaccensis) and snake fruit (Salacca zalacca) were also assessed for carbon storage ability in comparison with LiDAR data. A random systematic sampling method was used for conducting the forest inventory. Three square plots of 0.25 ha were established in each of the agroforestry system site. Soil were taken at the depth 0-5 cm, 5-10 cm and 10-30 cm. Shrub layer and organic layer were taken at five randomly selected positions in each plot. Field measured attributes such as height and DBH were measured and then converted into above ground biomass by using site specific allometric equation. carbon stocks were considered to be 50 percent of the total biomass. The results shows that forest have the highest carbon stock (287.38 tan C ha·1) in comparison with three oil palm agroforestry systems (79.12 tan C ha·1, 85.39 tan C ha·1 and 78.27 tan c ha·1) and monoculture oil palm plantation (76.44 tan C ha·1). In teak, agarwood and snake fruit agroforestry combination, the total carbon stock is 44.04 tan C ha·1 in which 70 percent of it were contributed by the teak stand. Significance correlation were also found for field measured height and LiDAR maximum height for teak and agarwood (R2 = 0.807, teak; R2 = 0.923, agarwood) in individual tree analysis. For plot level approach, canopy coverage percentage flor UDAR data shows strong correlation with above ground carbon of snake fruit (R2 = o. 756). This study found that agroforestry systems have great potential in carbon storage and carbon sequestration and the use of remote sensing technology offers were capable in improving above ground carbon stock estimates.